2016
DOI: 10.3847/2041-8205/829/1/l11
|View full text |Cite
|
Sign up to set email alerts
|

TRACING THE REIONIZATION EPOCH WITH ALMA: [C ii] EMISSION IN z ∼ 7 GALAXIES

Abstract: We present new results on [CII]158µm emission from four galaxies in the reionization epoch. These galaxies were previously confirmed to be at redshifts between 6.6 and 7.15 from the presence of the Lyα emission line in their spectra. The Lyα emission line is redshifted by 100-200 km s −1 compared to the systemic redshift given by the [CII] line. These velocity offsets are smaller than what is observed in z ∼ 3 Lyman break galaxies with similar UV luminosities and emission line properties. Smaller velocity shif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
209
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(239 citation statements)
references
References 35 publications
27
209
2
1
Order By: Relevance
“…In addition, Dunlop et al (2017) noted that the HST and ALMA astrometry of the HUDF presented both a systematic shift of 0 25 and a random offset of up to 0 5. Similarly, Pentericci et al (2016) note 0 1-0 6 random offsets measured from serendipitous detections in the field. Unfortunately, we do not detect any other sources in our small field of view to perform relative astrometric calibration.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, Dunlop et al (2017) noted that the HST and ALMA astrometry of the HUDF presented both a systematic shift of 0 25 and a random offset of up to 0 5. Similarly, Pentericci et al (2016) note 0 1-0 6 random offsets measured from serendipitous detections in the field. Unfortunately, we do not detect any other sources in our small field of view to perform relative astrometric calibration.…”
Section: Resultsmentioning
confidence: 94%
“…At z∼7, however, Stark et al (2015) measured an offset of Δv≈60 km s −1 between Lyα and CIV for a lensed lowluminosity galaxy A1703-zd6 at z=7.045 (though CIV might not trace systemic velocity). Pentericci et al (2016) reported velocity shifts of ∼100 km s −1 between [C II] and Lyα for their three most significant detections. For a higher-luminosity galaxy, Stark et al (2017) reported an offset between CIII] and Lyα of ∼340 km s −1 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Some recent observations suggest that five z ∼ 7 galaxies show very small velocity offsets about 20-150km s −1 between Lyα and [CII] emission lines (Pentericci et al 2016;Bradac et al 2017). Those small V(red-peak) values may indicate that the Lyα escape fractions are high and the optical depths of ISM and CGM are small.…”
Section: Predicting Lyα Escape Fractionmentioning
confidence: 99%
“…A similar shift is also observed at higher redshift. For instance, Pentericci et al (2016) observed shifts of 100-200 km s −1 between the Lyα and [C II] emission line in four galaxies at redshifts between 6.6 and 7.2. Likewise, the Lyα emission of the z∼6 star-forming galaxy A383-5.2 appears to be shifted by 120 km s −1 with respect to the systemic redshift probed via the C III] λ1909 metal line (Stark et al 2015).…”
Section: Tentative Detection Of An Extended Emissionmentioning
confidence: 99%